2007
DOI: 10.1104/pp.106.095158
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Complex II Is Essential for Gametophyte Development in Arabidopsis

Abstract: Mitochondrial complex II (succinate dehydrogenase [SDH]) is part of the tricarboxylic acid cycle and the respiratory electron transport chain. Its flavoprotein subunit is encoded by two nuclear genes, SDH1-1 and SDH1-2, in Arabidopsis (Arabidopsis thaliana). The SDH1-2 gene is significantly expressed only in roots, albeit at very low level, and its disruption has no effect on growth and development of homozygous mutant plants. In contrast, SDH1-1 transcripts are ubiquitously expressed, with highest expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 61 publications
(65 reference statements)
3
95
0
Order By: Relevance
“…According to the oxidative stress that Cu has been proposed to induce, one of the best representatives in this category was CSD1, which was already reported to respond to Cu status, and was confirmed by qPCR under our conditions. Moreover, the expression of a nuclear gene encoding the flavoprotein subunit of succinate dehydrogenase, SDH1-2, 39 was also checked and confirmed (Fig. 2), indicating the mitochondrial involvement in the perception/ signalling of these oxidative stress conditions.…”
Section: Analysis By Real-time Quantitative Pcr Of the Representativementioning
confidence: 80%
“…According to the oxidative stress that Cu has been proposed to induce, one of the best representatives in this category was CSD1, which was already reported to respond to Cu status, and was confirmed by qPCR under our conditions. Moreover, the expression of a nuclear gene encoding the flavoprotein subunit of succinate dehydrogenase, SDH1-2, 39 was also checked and confirmed (Fig. 2), indicating the mitochondrial involvement in the perception/ signalling of these oxidative stress conditions.…”
Section: Analysis By Real-time Quantitative Pcr Of the Representativementioning
confidence: 80%
“…S5). TTFA and carboxin are generally described as complex II inhibitors in mammalian and plant systems, causing decreased SQR activity and mitochondrial respiration rates at high micromolar to millimolar concentrations (Byun et al, 2008;JardimMesseder et al, 2015;Le贸n et al, 2007;Miyadera et al, 2003;Ramsay et al, 1981). As noted previously, sensitivity of SQR to these inhibitors varies between different species; mammals show a very high sensitivity with IC 50 values in micromolar concentrations (Miyadera et al, 2003), whereas Arabidopsis SQR is less sensitive, showing inhibitory effects at millimolar concentrations (Supplemental Fig.…”
Section: Sa Likely Interacts With the Uq Binding Site Of Complex IImentioning
confidence: 96%
“…As noted previously, sensitivity of SQR to these inhibitors varies between different species; mammals show a very high sensitivity with IC 50 values in micromolar concentrations (Miyadera et al, 2003), whereas Arabidopsis SQR is less sensitive, showing inhibitory effects at millimolar concentrations (Supplemental Fig. S5; Le贸n et al (2007); Jardim-Messeder et al (2015). It has also been shown that TTFA binds to a site within SDH3/4 based on x-ray crystallography (Sun et al, 2005).…”
Section: Sa Likely Interacts With the Uq Binding Site Of Complex IImentioning
confidence: 98%
See 2 more Smart Citations